Catalytic Ammonia Combustion: Legacy Catalytic Burner Designs and Catalyst Requirements for In Situ Hydrogen Production - Khalid Al Sadi; Ebrahim Nadimi; Dawei Wu (Energies, 2025)
Ammonia is increasingly recognised as a promising carbon-free fuel and hydrogen carrier due to its high hydrogen content, ease of liquefaction, and existing global infrastructure. However, its direct utilisation in combustion systems poses significant challenges, including low flame speed, high ignition temperature, and the formation of nitrogen oxides (NOX). This review explores catalytic ammonia cracking as a viable method to enhance combustion through in situ hydrogen production. It evaluates traditional catalytic burner designs originally developed for hydrocarbon fuels and assesses their adaptability for ammonia-based applications. Special attention is given to ruthenium- and nickel-based catalysts supported on various oxides and nanostructured materials, evaluating their ammonia conversion efficiency, resistance to sintering, and thermal stability. The impact of the main operational parameters, including reaction temperature and gas hourly space velocity (GHSV), is also discussed. Strategies for combining partial ammonia cracking with stable combustion are studied, with practical issues such as catalyst degradation, NOX regulation, and system scalability. The analysis highlights recent advancements in structural catalyst support, which have potential for industrial-scale application. This review aims to provide future development of low-emission, high-efficiency catalytic burner systems and advance ammonia’s role in next-generation hydrogen energy technologies.